Answer:
a. -5
b.-5
c.-5
Step-by-step explanation:
In order to find the average rate of change of a function , we divide the change in the output value by the change in the input value.
Generally, the average rate of change (ARC) on an ecuatios between two points (x1,f(x1)) and (x2,f(x2)) is
- ARC = [f(x2)-f(x1)]/ (x2-x1)
<em>In case a)</em>
f(-1)= -5*(-1)-8=5-8= -3 f(3)= -5*3-8= -23
Then ARC= (-23-(-3))/(3-(-1))=-20/4=-5
<em>In case b)</em>
f(a)= (-5a-8)
f(b)= (-5b-8)
Then ARC= [(-5b-8)-(-5a-8)]/(b-a)= (-5b+5a)/(b-a)= -5(b-a)/(b-a)= -5
<em>In case c)</em>
f(x)= -5x-8
f(x+h)= -5(x+h)-8= -5x-5h-8
then ARC= [(-5x-5h-8)-(-5x-8)]/(x+h-x) =-5h/h= -5
if there are 300 raffle tickets and one raffle ticket is drawn, the proabability of drawing the next one is 1 in 299 because there is one less ticket from the previous win
Answer:
-q
Step-by-step explanation:
We know that we are trying to find an expression equivelant to p - q:
p - q can be p - 1q
We can then put parenthesis around -1q:
p + (-1q)
We then can simplify:
p + (-q)
Your answer is c, common sense
person number 60
10 20 30 40 50<u> 60</u>
12 14 36 48<u> 60</u>
It id in both of their times tables.<u />